Penerapan Media Pembelajaran Interaktif Dapat Meningkatkan Hasil Belajar IPS di Kelas VI SDN Pagagan 1 Kecamatan Pademawu Kabupaten Pamekasan Tahun Pelajaran 2019/2020 - Mohammad Ali Santoso (Journal on Education, 2023)
Image media is one of the learning media tools that is seen as able to provide a learning experience that is directly related to the object being studied. In other words, one way to increase students' understanding of changes in provincial areas in Indonesia is through the use of learning media in the form of map images.This study aims to: describe the use of interactive learning media to improve social studies learning outcomes in changes in provincial areas in Indonesia, describe the level of mastery of student learning about changes in provincial areas in Indonesia by using interactive learning media in social studies class VI at SDN Pagagan 1 Pademawu District.The use of the use of interactive learning media can improve social studies learning outcomes for changes in provincial areas in Indonesia for class VI, the highest score achieved by students reaches 100 (2 people). VI at SDN Pagagan 1, Pademawu District. Of the 20 students, there were 90% or 18 students who had completed their studies and only 2 students (10%) had not completed their studies.